Mengembangkan Pembelajaran PAIKEM pada Anak Usia 6-13 Tahun di Gereja Isa Al-masih - Esra Zos Samosir; Desetina Harefa; Ellyzabeth Sinaga; Megariana Megariana; Dewi Lidya S (Real Kiddos: Jurnal Pendidikan Anak Usia Dini, 2023)
This research began with Sunday school children who were less enthusiastic about attending worship and complaints from parents and teachers of Sunday school children of Isa Al-Masih Baloi Kolam church, which led to concerns about children's spiritual growth. This research was written using qualitative methods with a descriptive approach. The purpose of this research is to develop PAIKEM learning methods for children aged 6-13 years at Isa Al-Masih church to increase children's enthusiasm in worship. The novelty of this research is to develop a method of teaching PAIKEM to children aged 6-13 years in increasing children's interest and willingness to worship. This research is useful for reaching children aged 6-13 years in the church of Isa Al-Masih in cultivating the spirituality of Sunday school children.Keywords: Sunday school children; the era of digitalization; PAIKEM AbstrakPenelitian ini bermula dari anak-anak sekolah minggu yang kurang antusias untuk hadir beribadah serta adanya keluhan orang tua dan guru dari anak sekolah minggu gereja Isa Al-masih Baloi Kolam, yang berujung kepada kekhawatiran terhadap pertumbuhan spiritualitas anak. Penelitian ini ditulis menggunakan metode kualitatif dengan pendekatan deskriptif. Tujuan penelitian ini ialah mengembangkan metode pembelajaran PAIKEM bagi anak usia 6-13 tahun di gereja Isa Al-masih untuk meningkatkan antusias anak dalam beribadah. Kebaharuan penelitian ini ialah untuk mengembangkan metode mengajar PAIKEM pada anak usia 6-13 tahun dalam meningkatkan minat dan kemauan anak untuk beribadah. Penelitian ini bermanfaat untuk menjangkau anak usia 6-13 tahun di gereja Isa Al-masih dalam menumbuhkan spiritualitas anak sekolah minggu.Kata Kunci: anak sekolah minggu; era digitalisasi; PAIKEM